2009
DOI: 10.1002/jbm.a.32463
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide nanotubes enhance bone bonding in vivo

Abstract: Implant topography is critical to the clinical success of bone-anchored implants, yet little is known how nano-modified implant topography affects osseointegration. We investigate the in vivo bone bonding of two titanium implant surfaces: titanium dioxide (TiO(2)) nanotubes and TiO(2) gritblasted surfaces. In previous in vitro studies, the topography of the TiO(2) nanotubes improved osteoblast proliferation and adhesion compared with gritblasted titanium surfaces. After four weeks of implantation in rabbit tib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
237
1
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 336 publications
(266 citation statements)
references
References 20 publications
16
237
1
8
Order By: Relevance
“…Investigators are refining dental implants by the addition of nano tubes to the outward of the implant. It increases the capability to load the nanotubes with antiinflammatory drugs that can be applied directly to the area around the implant [39]. Silver nanoparticles have gained an ever increasing attention in orthopaedics due to their promising antimicrobial features.…”
Section: Orthodontology and Orthopedicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators are refining dental implants by the addition of nano tubes to the outward of the implant. It increases the capability to load the nanotubes with antiinflammatory drugs that can be applied directly to the area around the implant [39]. Silver nanoparticles have gained an ever increasing attention in orthopaedics due to their promising antimicrobial features.…”
Section: Orthodontology and Orthopedicsmentioning
confidence: 99%
“…Number of studies have been reported in past few years related to the efficacy and safety of various nanoparticles like cholesteroltethered platinum II-based supramolecular nanoparticle [37][38][39][40][41], polymeric-ceramic nanocarriers (NCs) in order to achieve oral delivery of the anticancer neutraceutical iron-saturated bovine lactoferrin (Fe-bLf) protein) [42,43], novel alginate-enclosed chitosan-calcium phosphate-loaded iron-saturated bovine lactoferrin nanocarriers for oral delivery in colon cancer therapy etc. [44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Researches demonstrate that the nanotubes accelerate osteoblast adhesion and growth [5] , enhance apatite deposition [6], exhibit excellent bioactivity [7], improve bone bonding in vivo [8], demonstrate better corrosion resistance [9] and can be a drug delivery vehicle [10]. TiO 2 nanotube layer can be produced by many methods, including template-assisted methods , sol-gel techniques, and hydro/solvothermal methods (with or without templates) [11].…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently, it has been reported that surfaces with nano features, either disordered 6,7 or ordered (e.g. gold nanoparticle arrays, 8 titanium nanotube arrays, [9][10][11][12] chemically etched titanium surfaces, 13,14 and nanostructured tantalum surfaces) [15][16][17] can greatly improve cell adhesion, proliferation and differentiation. 18 Our group has developed a general nano-patterning method for metal surfaces that is inexpensive as well as time-efficient.…”
Section: Introductionmentioning
confidence: 99%